Implementasi Kode Etik Mahasiswa dalam Berbusana di Fakultas Ekonomi dan Ilmu Sosial Universitas Islam Negeri Sultan Syarif Kasim Riau - Rahmadani, Suci; Wahyudi, Rodi (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to determine the implementation of the student code of ethics in dressing at the Faculty of Economics and Social Sciences, Sultan Syarif Kasim State Islamic University, Riau. This research uses a qualitative method with a descriptive approach which is strengthened by the results of interviews.  The research results show that female students have received socialization about the dress code of ethics from lecturers when they first entered campus. The dress code of ethics that is most often violated by female students is tucking their clothes into their skirts. The parties who often reprimand students who violate the dress code of ethics are lecturers.  Female students who violate the dress code of ethics still do not receive strict sanctions because they still take the form of a verbal warning and are told to go home to change clothes according to the code of ethics.